Reproductive traits and population dynamics of benthic invertebrates indicate episodic recruitment patterns across an Arctic polar front - Reed, Adam J. (Ecol Evol, 2021)
Climate‐induced changes in the ocean and sea ice environment of the Arctic are beginning to generate major and rapid changes in Arctic ecosystems, but the effects of directional forcing on the persistence and distribution of species remain poorly understood. Here, we examine the reproductive traits and population dynamics of the bivalve Astarte crenata and sea star Ctenodiscus crispatus across a north–south transect that intersects the polar front in the Barents Sea. Both species present large oocytes indicative of short pelagic or direct development that do not differ in size–frequency between 74.5 and 81.3º latitude. However, despite gametogenic maturity, we found low frequencies of certain size classes within populations that may indicate periodic recruitment failure. We suggest that recruitment of A. crenata could occur periodically when conditions are favorable, while populations of C. crispatus are characterized by episodic recruitment failures. Pyloric caeca indices in C. crispatus show that food uptake is greatest at, and north of, the polar front, providing credence to the view that interannual variations in the quantity and quality of primary production and its flux to the seafloor, linked to the variable extent and thickness of sea ice, are likely to be strong determinants of physiological fitness. Our findings provide evidence that the distribution and long‐term survival of species is not only a simple function of adaptive capacity to specific environmental changes, but will also be contingent on the frequency and occurrence of years where environmental conditions support reproduction and settlement.